The Image of Somebody Else’s Speech in the Narrator’s Speech - Шульская, О. В. (Kalbotyra, 1997)
The present paper deals with the means of introduction somebody else’s speech into the narrator’s speech. The analysis draws upon the verses of contemporary poets. The range of the said means encompasses the introduction of somebody else’s words, their original expression intact, as well as the introduction of different voices which are later filled with dialogic and stylistic colouring. The analysis of the image of somebody else’s speech in the narrator’s speech provides the grounds for more through insights both into the image of the lyrical hero and the peculiarities of the poetic style.